(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
A new tripodal tris-chelating carbacylamidophosphate (CAPh) ligand (H3L = N(CH2CH2N(H)C(O)N(H)P(O)(OCH3)2)3) has been synthesized and a series of coordination compounds of general formula LnL (where Ln = La, Nd, Eu, Tb) based on this ligand has been obtained and isolated in the crystalline state. The resulting compounds have been investigated by the means of thermal gravimetric analysis, 1H NMR, IR and UV-Vis absorption spectroscopy. The ligand and all complexes are soluble in water, poorly soluble in methanol and isopropanol, insoluble in nonpolar solvents. It was found, that each Ln(III) ion of the complexes under consideration is bonded with oxygen atoms belonging to the phosphoryl and carboxyl groups of three bidentate chelated coordinating arms of the ligand (six lanthanide-oxygen bonds totally). In the 1H NMR spectrum of lanthanum coordination compound (LаL) all signals are shifted in the region of a strong field compared to analogous signals in the respective H3L spectrum, which can be explained by the redistribution of electronic density in the ligand due to deprotonation. The fine structure of the supersensitive transitions in the electronic spectrum of the synthesized neodymium complex proves in favor of the coordination number 8. In the region of 4I9/2 → 2P1/2 transition (425–435 nm) a single absorption band is observed, indicating the presence of only one absorption center. The thermal stability of NdL complex has been investigated and the presence of two coordinated water molecules in the synthesized complexes has been established. Thus, coordination number of lanthanide ions is equal to eight (coordination formula [LnL(H2O)2]) which is in agreement with electronic spectroscopy results. Based on the data of the TGA for the coordination compound [NdL(H2O)2] one can conclude that significant mass loss occurs in one step. The complex compound begins to decompose above 200°C. Considerable mass loss continues to a temperature of 380–400°С. The DTA curve shows an exothermic effect at a temperature of 287°C, which can be connected with the oxidation processes.